Esthetics in Removable Partial Denture - A Review - Shah, R; Aras, M (Kathmandu University Medical Journal, 2015)
Removable partial denture is a repulsive modality of treatment that we still must rely upon for certain cases and is a part of the practice. But these patients expect it to look as esthetic as any other contemporary modality of treatment. This article thus focuses on the esthetic aspects that a clinician must place emphasis upon during the designing and fabrication of prosthesis to provide the desirable outcome.Kathmandu Univ Med J 2013; 11(4): 344-348